Sensory experiments : psychophysics, race, and the aesthetics of feeling - Fretwell, Erica, 1982- (Duke University Press, 2020)
"In SENSORY EXPERIMENTS Erica Fretwell considers the science of psychophysics, the study of sensory experience, in mid-nineteenth century America. In particular, Fretwell traces the development of "perceptual sensitivity," a metric of an individual's capacity to perceive finer feelings, in order to differentiate individuals on their ability to interpret their surroundings-and, subsequently, to buttress racist and eugenicist thought. Fretwell argues that perceptual sensitivity also led to an aesthetic sensibility, which she calls "psychophysical aesthesis." Through attention to slight gradations in sensory experiences that acquired significant social meaning, this speculative scientific discourse became an aesthetic point of view, one that lent itself to a hierarchical, racialized social order. The book considers both nineteenth-century and contemporary texts to show how psychophysics racialized aesthetics. Each chapter is devoted to one of the five senses (with short interludes exploring moments when the senses shade into each other). The chapters are arranged according to the hierarchy of senses that psychophysics and other sensory sciences had established - from the supposedly more refined or elevated senses of sight and sound to the more embodied ones of taste and touch. Chapter 3 is devoted to smell; here Fretwell considers how the aestheticization of smell elevated perfumery from an indulgence of baser instincts to an experimental science of scent. Fretwell shows how the sensibility conveyed in the cultural reception of newly artificial, synthesized perfumes corresponds to Kate Chopin's stylized and sensual portrayal of women in The Awakening. In chapter 4 Fretwell considers taste, where the affective relation between the consumer and the consumed was considered to be far more visceral. The chapter is organized around the idea of sweetness, a taste both developed and racialized not only by psychophysical discourses but also by the material realities of plantation slavery itself. Molasses and sugar came to occupy different places in the hierarchies of taste and race; Fretwell traces through the poems and the recipes of Emily Dickinson, whose lyrical appeals to an imagined sensuous indulgence in blackness reflect this logic. Fretwell concludes by considering the many ways in which sensory aesthetics continue to animate valuation of not only of tastes and pleasures, but also of all aspects of human lives"--